2016
DOI: 10.1080/02770903.2016.1193601
|View full text |Cite
|
Sign up to set email alerts
|

Does the use of efficacy or effectiveness evidence in cost-effectiveness analysis matter?

Abstract: 25 cost-effectiveness studies were included. Ten (40.0%) studies were effectiveness-based, yet 15 (60.0%) studies were efficacy-based. Of 17 studies using endpoints that could be compared to WTP threshold, 7 out of 8 (87.5%) effectiveness-based studies yielded favorable cost-effectiveness results, whereas 4 out of 9 (44.4%) efficacy-based studies yielded favorable cost-effectiveness results. The adjusted odds ratio was 15.12 (95% confidence interval; 0.59 to 388.75) for effectiveness-based versus efficacy-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Differences in baseline characteristics likely translate to differences in treatment costs and cost-offsets, which would in turn affect ICERs and, therefore, should routinely calculate ICERs by baseline risk. Compared with CEAs that utilize risk and efficacy estimates based on real world data (RWD), those based on clinical trial evidence often generate higher ICERs 25,26 . Several agencies have recommended using RWD to assess baseline risk and efficacy in CEA 2,[27][28][29] .…”
Section: Differences In Patient Characteristics By Baseline Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in baseline characteristics likely translate to differences in treatment costs and cost-offsets, which would in turn affect ICERs and, therefore, should routinely calculate ICERs by baseline risk. Compared with CEAs that utilize risk and efficacy estimates based on real world data (RWD), those based on clinical trial evidence often generate higher ICERs 25,26 . Several agencies have recommended using RWD to assess baseline risk and efficacy in CEA 2,[27][28][29] .…”
Section: Differences In Patient Characteristics By Baseline Riskmentioning
confidence: 99%
“…For example, despite the often debilitating effects of a migraine 39 , adherence and persistence to commonly prescribed prophylactic oral medications for episodic and chronic migraine are poor (<80%) and long-run (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) week) discontinuation rates are high ( 45%) in both randomized control trials (RCT) and real-world/community settings 40 . In two large RCTs, discontinuation rates for less frequently (every 12 weeks) administered injected onabotulinumtoxin A at 24 weeks was relatively low (10.4%) 41,42 .…”
Section: Adherencementioning
confidence: 99%
“…better) than the RCT-based CE model. A review of 25 studies of asthma treatments, which compared CE models using RWD vs RCT data, found that studies which relied on RWD were twice as likely to conclude that a treatment was cost-effective 12 . Additionally, the UK's National Institute of Clinical Excellence Decision Support Unit recently published a report outlining the need to use RWD when estimating absolute treatment effects 13 .…”
mentioning
confidence: 99%